Analysis of the indices of concentration and inequality of the brazilian exports of Erva-mate (Ilex paraguariensis St. Hill) Análise dos índices de concentração e desigualdade das exportações brasileiras de Erva-mate (Ilex paraguariensis St. Hill) - Oliveira G.S.* (2017)
© 2017.The objective of this study was to analyze the concentration and inequality measures for exports of Erva-mate in Brazil from 2005 to 2015. The Hirschman- Herfindahl Index (HHI) and the Bain Index were determined for concentration, with exports by Concentration in the four largest trading partners. For the calculation of inequality, the Gini Index was used, which showed stability throughout the evaluation period, characterized by a very strong to absolute inequality.